Pendidikan Keluarga dan Implikasinya terhadap Pembentukan Kepribadian - Wendy, Novrizal (Al-Riwayah : Jurnal Kependidikan, 2017)
The family is the first place for the child to receive an education and coaching. Although the school specializes educational activities, it does not start from a vacuum. Because schools accept children after going through various experiences and attitudes and patterns of behavior and skills gained from the family environment. Implementation of religious education to children in families at an early stage have a very large degree of urgency, given the role played by institutions of formal education, are not able to replace the family institution. Similarly, the education curriculum materials, including religious education curriculum in formal educational institutions still tend to be oriented only filling the brain with a number of knowledge, rather than planting religious moral values. That phenomenon makes the implementation of religious education in the family take place strategic position, which is in addition to invest the basis of religious moral values to children also complements the deficiencies of the formal education system. Provision of basic capital religious education to children in the family can give implications as follows: a) children have a basic knowledge of religion, b) children have a basic knowledge of morals, and c) children have a basic knowledge of social. The basic knowledge plays importance rule in achieving the main goals of Islamic education, the planting of faith and good behavior